2015
DOI: 10.7567/jjap.54.10nd10
|View full text |Cite
|
Sign up to set email alerts
|

Grain size effect on phase transition behavior and electrical properties of (Bi1/2K1/2)TiO3piezoelectric ceramics

Abstract: Dense and phase-pure (Bi 1/2 K 1/2 )TiO 3 (BKT) ceramics with various grain sizes from 0.18 to 1.01 µm were prepared by conventional sintering of a hydrothermally synthesized fine powder. The decrease in grain size resulted in the reductions in tetragonality, remanent polarization, and the piezoelectric d 33 coefficient, whereas the room-temperature dielectric permittivity slightly increased with decreasing grain size. The measurement of the temperature dependence of permittivity revealed that BKT exhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The value of ¾ r value reaches maximum (¾ m ), corresponding to the transition from spontaneous relaxor to paraelectric state, and is expressed as T m . 1), 26) For all ceramics, the depolarization temperature T d and T m are insensitive to the sintering temperature, T d holds on a narrow range from 205225°C and T m hold on 380°C. Figure 8 depicts the PE loops and JE curves at 1 Hz for the BKMS ceramics sintered in the temperature range of 10201050°C.…”
Section: Resultsmentioning
confidence: 96%
“…The value of ¾ r value reaches maximum (¾ m ), corresponding to the transition from spontaneous relaxor to paraelectric state, and is expressed as T m . 1), 26) For all ceramics, the depolarization temperature T d and T m are insensitive to the sintering temperature, T d holds on a narrow range from 205225°C and T m hold on 380°C. Figure 8 depicts the PE loops and JE curves at 1 Hz for the BKMS ceramics sintered in the temperature range of 10201050°C.…”
Section: Resultsmentioning
confidence: 96%
“…However, BKT powders synthesized by conventional solid-state reactions have been reported to decompose into K-rich and Bi-rich secondary phases upon prolonged sintering longer than 20 h, resulting in the degradation of the electric insulation property of these sintered ceramics [3,7]. On the other hand, we have reported that BKT powders derived by hydrothermal methods show good sinterability owing to their fine particle size (∼150 nm) and high chemical stability against prolonged sintering [6,8,9]. Sintering this hydrothermal powder for long periods (up to 100 h) can yield dense BKT ceramics with controlled grain sizes up to 1 m without noticeable formation of secondary phases [6,9].…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that the ferroelectric and piezoelectric properties of BKT are decreased in fine-grained ceramics with grain sizes lower than 1 m [5,6]. Thus, preparing ceramic samples with large grain sizes over 1 m is necessary for studying the intrinsic properties of BKT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) Recently, we developed a process for fabricating dense BKT ceramics via the normal sintering of hydrothermally derived BKT fine powders. 17) Electrical measurements of these high-quality BKT ceramics revealed that they possess a high depolarization temperature of approximately 300°C and a high piezoelectric constant d 33 of approximately 100 pC/N, 10),13), 14) suggesting that BKT-based ceramics are highly promising materials for piezoelectric applications.…”
Section: Introductionmentioning
confidence: 99%